Fragmentation of Irrigated and Rainfed Paddy Field in Cianjur Regency, West Java - Khursatul Munibah; La Ode Syamsul Iman; Rani Yudarwati; Diendra Abdul Karim; Indah Purnama Sari (Jurnal Ilmu Tanah dan Lingkungan, 2022)
Paddy field is the agriculture land that produces rice and needs to be protected because of the threat of high conversion. In the period 2003-2013, paddy field in West Java Province has decreased by 9098 ha, while all of Indonesia increased by 235 538 ha (2014) because of the new paddy field outside Java. In the period January-September 2022 national production reached 45.43 millian ton. Conversion of paddy field into built up area, especially in Java will affect to fragmentation level of paddy field themsefves. The purpose of this research is to analyze the fragmentation of irrigated and rainfed paddy field in Cianjur Regency. Fragmentation index that used in this research are Class Area (CA), Number of Patch (NumP), Mean Patch Size (MPS), Patch Size Standard Deviation (PSSD), Mean Sharp Index (MSI). The results showed that rainfed paddy field are more fragmented than irrigated paddy field, which is indicated by greater NumP values. Clutering of districts based on irrigated and rainfed paddy fields fragmentation index, each of which produces 3 groups . The high group has an increasingly fragmented tendency that identified by the high value of area (CA) and the number of patchs (NumP), while the other parameters are less able to characterize fragmentation difference. The fragmentation of irrigated and rainfed paddy fields in northern Cianjur Regency is influenced by the land conversion while in central and southern due to sloping topography.